Differential modulation of active expiration during hypercapnia by the medullary raphe in unanesthetized rats - Leirão, Isabela P. [UNESP]; Zoccal, Daniel B. [UNESP]; Gargaglioni, Luciane H. [UNESP]; da Silva, Glauber S. F. (Springer Nature, 2020)
Active expiration represents an important mechanism to improve ventilation in conditions of augmented ventilatory demand, such as hypercapnia. While a rostral ventromedullary region, the parafacial respiratory group (pFRG), has been identified as a conditional expiratory oscillator, little is known about how central chemosensitive sites contribute to modulate active expiration under hypercapnia. In this study, we investigated the influence of the medullary raphe in the emergence of phasic expiratory abdominal activity during hypercapnia in unanesthetized adult male rats, in a state-dependent manner. To do so, reverse microdialysis of muscimol (GABAA receptor agonist, 1 mM) or 8-OH-DPAT (5-HT1A agonist, 1 mM) was applied in the MR during sleep and wakefulness periods, both in normocapnic (room air) and hypercapnic conditions (7% CO2). Electromyography (EMG) of diaphragm and abdominal muscles was performed to measure inspiratory and expiratory motor outputs. We found that active expiration did not occur in room air exposure during wakefulness or sleep. However, hypercapnia did recruit active expiration, and differential effects were observed with the drug dialyses in the medullary raphe. Muscimol increased the diaphragm inspiratory motor output and also increased the amplitude and frequency of abdominal expiratory rhythmic activity during hypercapnia in wakefulness periods. On the other hand, the microdialysis of 8-OH-DPAT attenuated hypercapnia-induced active expiration in a state-dependent manner. Our data suggest that the medullary raphe can either inhibit or potentiate respiratory motor activity during hypercapnia, and the balance of these inhibitory or excitatory outputs may determine the expression of active expiration.
Keywords: Abdominal activity; Brainstem; Central chemoreception; Serotonin